Interlimb Coordination during Forward and Backward Walking in Primary School-Aged Children - Meyns, Pieter (Public Library of Science, 2013)
Previous studies comparing forward (FW) and backward (BW) walking suggested that the leg kinematics in BW were essentially those of FW in reverse. This led to the proposition that in adults the neural control of FW and BW originates from the same basic neural circuitry. One aspect that has not received much attention is to what extent development plays a role in the maturation of neural control of gait in different directions. BW has been examined either in adults or infants younger than one year. Therefore, we questioned which changes occur in the intermediate phases (i.e. in primary school-aged children). Furthermore, previous research focused on the lower limbs, thereby raising the question whether upper limb kinematics are also simply reversed from FW to BW. Therefore, in the current study the emphasis was put both on upper and lower limb movements, and the coordination between the limbs. Total body 3D gait analysis was performed in primary school-aged children (N = 24, aged five to twelve years) at a preferred walking speed to record angular displacements of upper arm, lower arm, upper leg, lower leg, and foot with respect to the vertical (i.e. elevation angle). Kinematics and interlimb coordination were compared between FW and BW. Additionally, elevation angle traces of BW were reversed in time (revBW) and correlated to FW traces. Results showed that upper and lower limb kinematics of FW correlated highly to revBW kinematics in children, which appears to be consistent with the proposal that control of FW and BW may be similar. In addition, age was found to mildly alter lower limb kinematic patterns. In contrast, interlimb coordination was similar across all children, but was different compared to adults, measured for comparison. It is concluded that development plays a role in the fine-tuning of neural control of FW and BW.